Laplace Transform and Finite Difference Method for Solving Problems of Mechanical Systems - Keng You Seng; Syahirbanun Isa (Enhanced Knowledge in Sciences and Technology, 2024)
This research explores the application and efficiency of the Laplace transform and the finite difference method on several mechanical systems. The mechanical systems utilised in this research can be divided into three types, namely, homogenous, non-homogenous, and non-linear. The numerical results obtained using both Laplace transform and the finite difference method are compared in terms of absolute error, and graphically illustrated using MATLAB 2023. The results show that the absolute errors between both methods are extremely small.